Factor Analysis Of Third Trimester Pregnant Women's Perceptions And The Influence Of Abstinence From Sexual Intercourse - Rismayana Rismayana; Cakrawati R Cakrawati R (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Pregnancy is a physiological process accompanied by physical, psychological, hormonal, and social changes. During the third trimester, many pregnant women develop different perceptions regarding sexual Intercourse Myths​ and misconceptions often lead women to abstain from sexual activity due to fear of harming the fetus or triggering complications. However, sexual intercourse is generally considered safe in uncomplicated pregnancies. Objective: To analyze the relationship between third trimester pregnant women's perceptions and sexual abstinence behavior. Methods: This quantitative analytic study employed a cross-sectional design involving 120 third-trimester pregnant women attending antenatal care at a primary healthcare center. Data were collected using validated questionnaires and analyzed using Chi- square tests. Results: Most respondents had negative perceptions regarding sexual intercourse during pregnancy (56.7%), while 61.7% reported abstaining from sexual intercourse. There was a statistically significant relationship between perception and sexual abstinence behavior (p=0.001). Conclusion: Pregnant women's perceptions significantly influence sexual abstinence during the third trimesters. Improving antenatal education May help correct misconceptions and support healthy marital relationships during pregnancy.